Penerapan Workbook Matematika Berbasis Kontekstual - Tri Candra Wulandari; Sri Rahayu (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2017)
Mathematics in primary schools still rely on textbooks and workbooks students were also issued by the government. In general, it seems simpler both from the teachers and students, because students only carry one book that contains a variety of subjects. Weak concept is very pronounced in mathematics. In integrated math into the thematic lessons, however, mathematics remains one of the subjects tested on a final school examinations. Teachers are preparing for the final exam had to work hard to repeat concepts ranging from grade 1 to grade 5. Therefore, it is necessary for teachers of proven strategies so that the material presented can be accepted students well. This research purposed to describe the application of contextual learning using math workbook. This study uses qualitative research with 30 research subjects third grade elementary school students in SDN Gandang I Malang. Data collection technique used documentation techniques and tests. Data analysis technique used qualitative descriptive analysis. After implementing the learning using the workbook, the average repeat is 86.96, the lowest score and the highest score each are 70 and 100. Based on the results obtained, contextual workbook that directly relate to the theme 7 that the energy source can be applied to the study of mathematics the third class at SDN Gadang I Malang.